Strategies to Improve Bone Healing: Innovative Surgical Implants Meet Nano-/Micro-Topography of Bone Scaffolds - Dirk Wähnert; Johannes Greiner; Stefano Brianza; Christian Kaltschmidt; Thomas Vordemvenne; Barbara Kaltschmidt (Biomedicines, 2021)
Successful fracture healing is dependent on an optimal mechanical and biological environment at the fracture site. Disturbances in fracture healing (non-union) or even critical size bone defects, where void volume is larger than the self-healing capacity of bone tissue, are great challenges for orthopedic surgeons. To address these challenges, new surgical implant concepts have been recently developed to optimize mechanical conditions. First, this review article discusses the mechanical environment on bone and fracture healing. In this context, a new implant concept, variable fixation technology, is introduced. This implant has the unique ability to change its mechanical properties from “rigid” to “dynamic” over the time of fracture healing. This leads to increased callus formation, a more homogeneous callus distribution and thus improved fracture healing. Second, recent advances in the nano- and micro-topography of bone scaffolds for guiding osteoinduction will be reviewed, particularly emphasizing the mimicry of natural bone. We summarize that an optimal scaffold should comprise micropores of 50–150 µm diameter allowing vascularization and migration of stem cells as well as nanotopographical osteoinductive cues, preferably pores of 30 nm diameter. Next to osteoinduction, such nano- and micro-topographical cues may also reduce inflammation and possess an antibacterial activity to further promote bone regeneration.